2018
DOI: 10.1177/0954408918774771
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the metal-to-metal contact flange joint subject to external bending moment

Abstract: Metal-to-metal contact flange joints are widely used in nuclear and petrochemical industry for severe conditions, because of the relative stability of the sealing gasket stress under complex service condition. In the present work, finite element models were used for analyzing the stress distribution of metal-to-metal contact pipe flange connection under different internal pressures, temperatures, and external bending moments to evaluate the sealing and strength performance. A metal-to-metal contact pipe flange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The actual joint leakage is thus the net effect of these two competing factors, and therefore, the ability of a gasket to sustain high compressive loads is essential to the control of leakage in a bolted joint. Zhang et al [22] evaluated the sealing and strength performance, finite element models were used for analyzing the stress distribution of metalto-metal contact pipe flange connection, the result showed that the maximum allowance bending moment was determined by the strength criterion. Bouzid et al [23,24] established a leakage model of porous gasket under different medium gases.…”
Section: Introductionmentioning
confidence: 99%
“…The actual joint leakage is thus the net effect of these two competing factors, and therefore, the ability of a gasket to sustain high compressive loads is essential to the control of leakage in a bolted joint. Zhang et al [22] evaluated the sealing and strength performance, finite element models were used for analyzing the stress distribution of metalto-metal contact pipe flange connection, the result showed that the maximum allowance bending moment was determined by the strength criterion. Bouzid et al [23,24] established a leakage model of porous gasket under different medium gases.…”
Section: Introductionmentioning
confidence: 99%